Chitosan hydrogel‐coated cellulosic fabric for medical end-use: Antibacterial properties, basic mechanical and comfort properties. (1st January 2020) - Benltoufa, Sofien; Miled, Wafa; Trad, Mariem; Slama, Rihab Ben; Fayala, Faten
Highlights: The hydrogel bounded rate onto the surface was improved by a previous cellulosic chemical activation. A confirmed antibacterial activity against Escherichi coli, Listeria monocytogene and Staphylococcus aureus bacteria. The proposed treatment depends on the activation process. The used treatment caused slight decrease in air permeability and made the support thickener. No significant effect on breathability and basic comfort performances of fabric that could drawback with the medical use. Abstract: This study explores the influence of functionalization process of cellulosic structure on its mechanical and comfort properties. Chitosan hydrogel has been synthetized and applied on cellulosic fabric to impart pH-sensitivity and antimicrobial behavior. The hydrogel bounded rate onto the surface was enhanced by a previous chemical activation of cotton fabric. Antimicrobial behavior was confirmed by investigation of the antibacterial activities against Escherichia coli, Listeria monocytogene and Staphylococcus aureus bacteria. The pH stimuli-responsiveness behavior was also conﬁrmed and the pH-dependency swelling of the chitosan hydrogel was successfully transformed into cellulosic sites. The resulting fabric was confirmed suitable for medical, surgical and also transdermal therapy applications. Meanwhile, these modifications have unexpectedly altered basic mechanical and comfort properties. It was established that the proposed antimicrobial treatment caused slight decrease in air permeability and made the support thickener. The obtained results revealed also that tensile behavior and the ultimate comfort properties were greatly influenced by the chemical activation.